Urban Solid Waste Management And Environmental Sustainability In Abakaliki Urban, Nigeria - Okwesili, Joseph; Chinyere, Ndukwe; Chidi Iroko, Nwuzor (European Scientific Journal, ESJ, 2016)
Waste management has become a common issue of discourse among individuals, groups and governments. This study which assessed urban solid waste management in Ebonyi state with focus on Abakaliki urban specifically sought to find out why indiscriminate solid waste disposal/dumps has persisted in Abakaliki urban, investigate the measures put in place to curtail the tide and ascertain the extent to which indiscriminate waste disposal affects people’s health and environment. Four null hypotheses were formulated and Human Capital Theory was adopted as the theoretical framework. The study used survey design whereby data were collected from the sample considered to be representative of the population. Taro Yameni’s formula was applied to reduce the initial population of 116,987 to a smaller researchable size of 399 while data were collected through structured questionnaire. The data collected were presented in tables containing frequencies of the responses and their corresponding percentages. The four hypotheses of the study were tested using chi-square (X2) statistical tool and the result of the analyses revealed that: there is currently no government approved dumpsites in Abakaliki metropolis, most communicable diseases are contracted from dirty environment, among others. The implications are that most households will soon be cut off by flood arising from the blockage of water channels, some streets and roads will be blocked by heaps of wastes and more epidemics will be contracted by the people if nothing urgent was done. The study concluded that, the Ebonyi State Environmental Protection Agency (EBSEPA) currently have no required manpower, technical skills and competences to curtail the tide of waste and therefore made the following recommendations: Ebonyi state government should strengthen the already established departments of Environmental and Health Sciences in Ebonyi State University (EBSU) and the School of Health Technology, Ezzamgbo, by providing and equipping them with modern waste management equipment for students to be exposed to practical methods of waste management, Government should contract foreign-based private firm through Public-Private-Partnership (PPP) arrangement to establish waste management industry in Ebonyi state, immediate provision of permanent waste dumpsites by the government, among others.